Laser spectroscopy : proceedings of the XVII international conference - Hinds, E. A.; Ferguson, Allister; Riis, Erling (World Scientific, 2005)
This volume is the latest proceedings of the International Conference on Laser Spectroscopy, a leading forum in the field for more than three decades. It features invited talks and selected contributions reflecting major advances in laser physics, laser spectroscopy, atomic cooling, and quantum information processing. A central theme is precision measurements, driven by rapid progress in laser technology and highlighted by contributions from Nobel Prize-winning pioneers. The volume also emphasizes research on cold atoms and quantum degenerate gases, marking the tenth anniversary of the first announcement of an atomic Bose-Einstein Condensate.